МІЖКУЛЬТУРНА КОМУНІКАЦІЯ ЯК ІНСТРУМЕНТ ПОПУЛЯРИЗАЦІЇ УКРАЇНСЬКОЇ КУЛЬТУРИ: ДОСВІД МІЖНАРОДНОГО ФЕСТИВАЛЮ - КОНКУРСУ «МИСТЕЦЬКІ ПРОМЕНІ УКРАЇНИ» - Королик-Бойко, Л. (Науковий альманах мистецтва та освіти, 2025)
У статті розкрито роль міжкультурної комунікації як важливого інструменту культурної дипломатії України у сучасному світі. На прикладі Міжнародного фестивалю-конкурсу “Мистецькі промені України” проаналізовано, як мистецькі проєкти сприяють утвердженню позитивного іміджу держави, популяризації українського мистецтва та духовної спадщини, розширенню творчих зв’язків і формуванню міжнародного партнерства.Мат. ІІ Міжнар. наук.-практ. конф. (м. Івано-Франківськ, 19–20 грудня 2024 р.). Івано-Франківськ, 2024. С. 132–134.ІІ Міжнародний фестиваль-конкурс «Мистецькі промені України».URL: https://www.facebook.com/groups/932160605061466 (дата звернення: 13.11.2025).II Міжнародний фестиваль-конкурс «Мистецькі промені України». URL: https://familytimes.com.ua/fiestival-konkurs-mistietski-promieni-ukrayini/ (дата звернення: 13.11.2025).The article reveals the role of intercultural communication as an important instrument of Ukraine’s cultural diplomacy in the modern world. Using the International Festival-Competition “Artistic Rays of Ukraine” as an example, it analyzes how artistic projects contribute to strengthening the country’s positive image, promoting Ukrainian art and spiritual heritage, expanding creative connections, and fostering international partnership. Proc. II International Scientific and Practical Conference (Ivano-Frankivsk, December 19–20, 2024). Ivano-Frankivsk, 2024. P. 132–134. II International Festival-Competition “Artistic Rays of Ukraine”. URL: https://www.facebook.com/groups/932160605061466 (access date: 13.11.2025).II International Festival-Competition “Artistic Rays of Ukraine”. URL: https://familytimes.com.ua/fiestival-konkurs-mistietski-promieni-ukrayini/ (access date: 13.11.2025).Олександр ПРИХОДЬКО, аспірант кафедри історії України, Полтавський національний педагогічний університет імені В. Г. Короленка, м. Полтава, УкраїнаORCID: 0000-0002-3932-8889o.p.prykhodko@pnpu.edu.uaНаціональні меншини як суб’єкти польсько-українських відносин у період Першої світової війниAbstract. The article focuses on the political processes associated with the involvement of national minorities in the Polish-Ukrainian relations during the First World War. It describes the main stages of the emergence of national liberation movements of Poles and Ukrainians and their cooperation and confrontation, as well as the attempts of the Central Powers to use ethnic groups to strengthen their own political influence.Keywords: national minorities, Poles, Ukrainians, Polish-Ukrainian relations, First World War, political processes.188